ANALISIS HUBUNGAN PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PT PINDAD ENJINIRING INDONESIA TUREN, MALANG - Pasaribu, Betsy; Chairus M. Nasution, Ute; Diana, Diana (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469), 2022)
The purpose of this study is to analyze the relationship of profitability, and firm size, to capital structure. The subject of this research is PT Pindad Engineering Indonesia. Data were collected using literature study and documentation techniques. The analysis was used using descriptive statistical analysis techniques. The data analyzed are in the form of a Balance Sheet and Income Statement for the period 2018-2020. The results showed that the company's capital structure increased in the 2018-2020 period and in the 2021 projection year the capital structure decreased by 0.08%. For the size of the company each period 2018-2021 has increased significantly, and for profitability has increased in the period 2018-2020 and decreased by 0.003% in the projected year 2021. Based on the results of the study, it can be concluded that profitability and company size have a relationship with the capital structure, which can be Judging from the profitability has a positive effect on capital structure, and firm size has a negative effect on capital structure. This shows that the management before setting the capital structure policy should first pay attention to the variables that affect the capital structure such as profitability, company size, liquidity, and company business risk. Company managers are expected to be able to consider funding decisions to be taken, both using their own capital and debt. The funding is expected to be able to meet the company's needs and can create an optimum Capital Structure.